2022
DOI: 10.2147/prbm.s375823
|View full text |Cite
|
Sign up to set email alerts
|

Who is More Likely to Report Medical Insurance Fraud in the Two Scenarios of Whether It Results in a Direct Loss of Individual Benefit? A Cross-Sectional Survey in China

Abstract: An individual's willingness to report is largely related to whether he or she is a direct victim. This study takes two scenarios of whether medical insurance fraud results in a direct loss of personal benefit and explores the differences in individuals' willingness to report and influencing factors in the two scenarios. Methods: In this study, questionnaires were used and participants were selected from 571 individuals in eastern, central, and western China. Analysis was performed using descriptive statistics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…In addition, this study explores the two dimensions of Perceived Risks (PRISK) and Perceived Consequences (PCONSE). PRISK is respondents' perceptions of risk after reporting [34], and PCONSE is respondents' perception of the consequences of health insurance fraud. The theoretical framework is illustrated in Fig.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…In addition, this study explores the two dimensions of Perceived Risks (PRISK) and Perceived Consequences (PCONSE). PRISK is respondents' perceptions of risk after reporting [34], and PCONSE is respondents' perception of the consequences of health insurance fraud. The theoretical framework is illustrated in Fig.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Willingness to report is the core prerequisite for promoting whistleblowing behavior, 17 , 18 and research on the public’s willingness to report medical insurance fraud is an important area of current interest among scholars. In 2022, Zhang, Zhang, Shi, Liu, Xu, Zhang, Wang, Tian, Wu, Kang 19 found that the public’s willingness to report medical insurance fraud was more related to whether they were direct victims. When medical insurance fraud causes a direct loss of personal benefit, the public is more likely to report it.…”
Section: Introductionmentioning
confidence: 99%